Le chemin des « mauvaises filles » - Véronique Blanchard; Hélène Duffuler-Vialle (Criminocorpus)
There were many methodological questions around the exhibition “ Bad girls”, presented by a team of researchers from several disciplines and of practitioners in special education. The first purpose was to combine and bring together the different disciplines in a specific scenography, to make the scientific research accessible, as subtle and complex as they are, without simplifying them too much. Another purpose was to embody the research, to develop it concretely by creating portraits of “bad girls” illustrated by their stories.After two years or preparation, the exhibition “Bad girls” was presented in a pedagogical and playful form: “snakes and ladders” with more or less “innocent girls”. The pawns are three young girls at different times and they demonstrate the historic aspect of the exhibition. The social way opened to the young girl by her education and by the machinery of justice and institution is often disrupted by various factors. Deviance, as considered by the criminal law, becomes a crime, is the core of the exhibition and takes the public to the different stalls of a fair, symbolic place of social danger, because of the concentration of persons from different classes, races et sexes. The different stalls show how the rules change according to the evolution of times and to the sexes. The exhibition shows also the institutional treatment of this deviance, a judicial, medical or social treatment, from the nineteenth century up till nowadays. The young innocent girl who, whatever her way, has necessarily deviated in some way, earns her freedom or gets trapped depending on the throw of the dice and the choices made by the visitors/players, who have several options at different stages of the play. The second part of the exhibition takes the public to a locked room where big photographs and copies of imprisoned girls’ words show the effect of confinement throughout the ages.The aim or the exhibition is tolerance and humanism. It was presented at Savigny-sur Orge, Roubaix and Lille. The public, made up of future social workers (educators, teachers), students, secondary school pupils and even schoolkids as well as individuals, during the guided tours and lectures, reacted in many interesting ways: awareness of the gender question, intense controversies on sexual violence and others. These reactions deserve to be related and analysed, as living testimonies of the effects of the spread of scientific research about a delicate and little-known subject : the violence used or suffered by young girls and their rebellion.This article is presented with photographs from the exhibition (snakes and ladders, stalls and panels) and photographs of the guided tours.